Peningkatan Pengetahuan Kelompok Tani melalui Pelatihan Budi Daya Porang di Desa Sugihwaras, Magetan, Jawa Timur - Adisti Permatasari Putri Hartoyo; Istomo Istomo; Sri Rahaju (Institut Pertanian Bogor, 2023)
The Subur farmer group is located in Sugihwaras Village, Maospati District, Magetan Regency, East Java which develops sugarcane (Saccharum officinarum) and teak (Tectona grandis) with a monoculture pattern. Monoculture cultivations produce a single income for farmers, hence other adaptive intolerant commodities and sites that generate alternative income are needed. One of them is Porang (Amorphophallus muelleri Blume). The farmer group’s knowledge and skills related to porang cultivation are very limited. The aims of this activity were: 1) To train farmer groups related to porang cultivation planted with agroforestry patterns; 2) To analyze knowledge changes of farmer groups regarding porang cultivation; and 3) To evaluate the implementation of the training program. The results showed that training on porang cultivation and making agroforestry demonstration plots were able to increase the knowledge of the Subur farmer group. The pre-test score was 65,1 (55%) while the post-test was 88,6 (75%). Based on the evaluation of the assessment of training activities by farmers, as many as 74,3% of farmers stated that they strongly agreed that the porang cultivation training was very useful and suitable for their needs. In addition, the activity feasibility analysis showed that this training is categorized as very feasible to be implemented with a score of 94%. Porang cultivation training for the Subur farmer group was able to increase knowledge and the potential to earn additional income for the people of Sugihwaras Village, Magetan Regency, East Java.